Analisis Kebijakan Luar Negeri Filipina Terhadap Cina Terkait Sengketa Laut Tiongkok Selatan pada Masa Duterte - Shintia Ramadani; Sofia Trisni (Intermestic: Journal of International Studies, 2019)
This article aims to identify and describe the Philippine foreign policy making process towards Chinese aggressiveness related to disputes between the two countries in the South China Sea. The Philippine foreign policy in the Duterte era was different from the previous administration. Authors use rational choice model of policy making from Charles Kegley and Shanon Blanton. While the method is qualitative with a descriptive approach and uses secondary data. In the discussion, the writer found that the policy makers, especially Duterte and supported by the Senate, had the motivation to maintain the great economic and security interests of China. Therefore, at the stage of policy making, the Philippines issued a rational policy that is cooperative in dealing with Chinese aggressiveness.